Fraud in modern banking: Highlights on online internet banking fraud - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2012)
This chapter is organized as follows: first, definitions, concept, and the motivations that lead fraudsters to execute fraudulent actions are clarified. Second, different types of fraud in the banking industry are observed with emphasis on online/internet banking fraud. In the third part, the detection and prevention of banking fraud especially the methods used to prevent online banking fraud are stated and the pros and cons of these methods are discussed. © 2012 Springer-Verlag Berlin Heidelberg. All rights are reserved.